2016
DOI: 10.1111/ajt.13560
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High-Mobility Group Box 1 in Rat Steatotic and Nonsteatotic Liver Transplantation From Donors After Brain Death

Abstract: † These authors contributed equally to this work.High-mobility group box 1 (HMGB1) has been described in different inflammatory disorders, and the deleterious effects of brain death (BD) may counteract the protection conferred by ischemic preconditioning (IP), the only surgical strategy that is being applied in clinical liver transplantation. Our study examined how HMGB1 may affect preconditioned and unpreconditioned steatotic and nonsteatotic liver grafts from donors after BD (DBDs) for transplantation. HMGB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Indeed, the role of ACh does differ in various pathologic states, proving advantageous in haemorrhagic shock, myocardial ischaemia and pancreatitis , but promoting inflammation and damage in chronic obstructive pulmonary disease . Our results for PH under I/R are nonetheless unlike than those detailed in previous reports of liver transplants from brain‐dead donors, whereby steatotic grafts were protected by ACh during prolonged (6‐hrs) cold ischaemia . This is expected because the systemic alterations induced by brain death (absent during PH under I/R), the extent and type of ischaemia ( i.e .…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, the role of ACh does differ in various pathologic states, proving advantageous in haemorrhagic shock, myocardial ischaemia and pancreatitis , but promoting inflammation and damage in chronic obstructive pulmonary disease . Our results for PH under I/R are nonetheless unlike than those detailed in previous reports of liver transplants from brain‐dead donors, whereby steatotic grafts were protected by ACh during prolonged (6‐hrs) cold ischaemia . This is expected because the systemic alterations induced by brain death (absent during PH under I/R), the extent and type of ischaemia ( i.e .…”
Section: Discussionmentioning
confidence: 93%
“…This is particularly problematic in LT from cadaveric donors because of the very short period of time available in which to pretreat them in this emergency procedure. Many of the previously mentioned studies (13 of 23) were performed in rat models with moderate steatotic livers . Of these studies,11 used fatty livers from Zucker rats; 5 used a methionine‐choline deficient diet and 5 a HFD, both models of steatohepatitis.…”
Section: Mechanisms Involved In Iri In Steatotic Ltmentioning
confidence: 99%
“…Given this, it would be extremely useful to make a clear distinction between the different types of steatosis (obesity/nutritionally induced versus alcoholic) for each surgical situation in order to design therapies that demonstrate its effectiveness under experimental conditions similar to those in the clinical setting. Moreover, few studies have closely mimicked the clinical practice of steatotic LT . In contrast, most studies reported I/R under normothermic conditions with or without hepatic resection .…”
Section: Mechanisms Involved In Iri In Steatotic Ltmentioning
confidence: 99%
See 2 more Smart Citations